The use of cognitive-behavioural therapy (CBT) in smoking cessation: a case study - Ab Raji, Nurul Atiqah; Mansor, Norwati; Mohd Karim, Anis Farahwahida; Ab Raji, Nurul Hidayah (UMT, 2019)
Recently, smoking habits among adolescents in Malaysia has increased and cigarette use remains common among youngsters. Ministry of Health, Malaysia (2015) has reported that 20% of smokers are among adolescents and there are 50 to 60 adolescent starts their smoking habit every day. Unfortunately, based on the report, it is also reported that 85% of them were remain as active smokers. Responding to this issue, the research understudy was conducted to investigate the effectiveness of Cognitive-Behavioural Therapy (CBT) techniques in smoking cessation. The target participant in this study was a Form Five Muslim male student at one of the secondary school in Kuala Lumpur. This study employed qualitative research design. Six individual counselling sessions within seven weeks were conducted by applying CBT techniques. The findings revealed that the client has a false belief about smoking and develop dependency on cigarettes whenever there is a symptom of stress. Thus, counsellor applied ‘cognitive restructuring’ technique in order to help the client to learn how to challenge his thoughts that leads him to light up cigarettes. Besides, counselor tried to strengthen client’s new behaviour by using positive-reinforcement. In short, this study suggests that the application of CBT techniques in smoking cessation is really helpful within a short time; the client had shown positive changes by quitting smoking at the end of the session.